Inspiratory muscle training improves maximal inspiratory pressure without increasing performance in elite swimmers - Gómez-Albareda, E.; Viscor, G.; García, I. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To analyze the effect of inspiratory muscle training (IMT) on the maximal inspiratory mouth pressure (MIP) and performance of elite swimmers.